Before catastrophe : the distinctive path of German zionism - Lavsḳi, Ḥagit 1980- (Wayne State Univ. Press [u.a.], 1996)
Studies the rise and decline of German Zionism between world war 1 and the rise of Nazism. Lavsky offers a detailed look at the ideological and political world that German Zionists inhabited and their role in building the yishuv. Zionism's